A prática do brincar na creche: uma análise crítica propositiva - Araujo, Ana Paula Gomes de (2021)
The object of this study is the act of playing at daycare. It aims to answer the following questions: What do the records from pedagogical practice of a daycare teacher/researcher indicate about playing? Do the records meet the established Toys and Games manual and the National Curriculum Guidelines and the National Common Curricular Base legislations? Its goal is to analyze the records from pedagogical practice of a teacher/researcher in regards to time and space for playing. For specific goals, it aims to verify what is brought by the records of the teaching practice of a daycare teacher about playing, verify if the records are aligned with the established Toys and Games manual, National Curriculum Guidelines and National Common Curricular Base legislations. The hipotesis brought is that playing is still misunderstood by kindergarten teachers , and, because of that, these moments are left aside in a school context. The universe of this search is a daycare centre set in the city of Santo André (SP). The subject is the kindergarten teacher/researcher that teaches 3 year old kids. It is about research of qualitative nature, and the means of collecting information are the records of the teacher/researcher about the playing of kids in different moments and spaces of daycare. The theoretical references are based on authors from toys and games, national curriculum guidelines, , national common curricular base legislations who broad the theme of knowledge: Tizuko Morchida Kishimoto, Adriana Friedmann, Gile Brougère, Lev Vygotsky. The informations reveal that the teacher/researcher allows lots of playing moments for the children, however, a great amount of times she interferes dealing with conflicts without waiting to see how they solve it themselves; forbids, in some occasions, more risky plays, like running, climbing trees and jumping, scared that the little ones might get hurt. Besides that, she also realized how a space that looks tedious by not having toys, can be potentializing in children's development. It lacks, by the coordination of this institution, a careful reading of the records so all the elements brought can be discussed with the teacher/ researcher and remade alongside with the children. Those reflexions enabled us to rethink the teaching practice in regards to playing on daycare.